3y-9+3-4y=y+y-18

Simple and best practice solution for 3y-9+3-4y=y+y-18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3y-9+3-4y=y+y-18 equation:


Simplifying
3y + -9 + 3 + -4y = y + y + -18

Reorder the terms:
-9 + 3 + 3y + -4y = y + y + -18

Combine like terms: -9 + 3 = -6
-6 + 3y + -4y = y + y + -18

Combine like terms: 3y + -4y = -1y
-6 + -1y = y + y + -18

Reorder the terms:
-6 + -1y = -18 + y + y

Combine like terms: y + y = 2y
-6 + -1y = -18 + 2y

Solving
-6 + -1y = -18 + 2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-2y' to each side of the equation.
-6 + -1y + -2y = -18 + 2y + -2y

Combine like terms: -1y + -2y = -3y
-6 + -3y = -18 + 2y + -2y

Combine like terms: 2y + -2y = 0
-6 + -3y = -18 + 0
-6 + -3y = -18

Add '6' to each side of the equation.
-6 + 6 + -3y = -18 + 6

Combine like terms: -6 + 6 = 0
0 + -3y = -18 + 6
-3y = -18 + 6

Combine like terms: -18 + 6 = -12
-3y = -12

Divide each side by '-3'.
y = 4

Simplifying
y = 4

See similar equations:

| -0.151=-0.008x+4.15 | | 8.3x-3.1(x-4)=-29.04 | | X=0.75+0.35 | | (x-5)(4x-9)=0 | | 5+1.5(d-1)=0.5 | | n^2+4n-10=0 | | 12m=20m+80 | | 3-4(x-2)=8x(2x-1) | | 4(x-3)+8=4(2x-6) | | (x+2)-(59-x)= | | 5-4a=a-13+-1a | | p=36inches | | (x+2)+(59-x)= | | m/2-3=-18 | | 3(10*2x)=25 | | j+j-12=2(j-12)+(2(j-12))-4 | | xy-5=2y+8 | | y=1.4x+4.4 | | -45=-2x-3+8x | | (2x+8)+(3x-28)= | | 5x-4(x+3)=7x+14 | | j+j-12=2(j-12)+2(j-12)+-4 | | 5v-32=8(v-7) | | X=2.5+2.8 | | ([2/3]*[v])^-3 | | 5x+y=o | | 5/7=125 | | 2x-3(2x+1)-10= | | 15-(6-g)= | | 2(x+2)-6=3x-19 | | x+14(2x+16)= | | h(1.7)=82-4.9(2.89) |

Equations solver categories